2008
DOI: 10.1089/jwh.2007.0625
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Factors in the Relationship between Income and Mammography Use in Low-Income Insured Women

Abstract: Aim: We used secondary data from a prospective randomized mammography recruitment trial to examine whether attitudinal and facilitating characteristics mediate the observed relationship between annual household income and mammogram receipt among women in an integrated health plan. Methods: We compared 1419 women due for a screening mammogram based on the 1995 annual household income poverty definition for a family of four (Ͻ$15,000 vs. Ͼ$15,000). A telephone survey was used to collect information on household … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Additional reported barriers to supplemental screening include lack of a primary care provider, lack of health insurance, associated out-of-pocket costs, anxiety related to MRI exams, and lack of social support, although these factors were not assessed in our study. 27 Multispecialty breast centers and full diagnostic radiology practices represented the most common practice types to offer breast MRI screening, reflecting their propensity for early adoption of advanced imaging modalities for new indications such as screening. 26 Most facilities offering supplemental MRI screening were also located in urban settings.…”
Section: Discussionmentioning
confidence: 99%
“…Additional reported barriers to supplemental screening include lack of a primary care provider, lack of health insurance, associated out-of-pocket costs, anxiety related to MRI exams, and lack of social support, although these factors were not assessed in our study. 27 Multispecialty breast centers and full diagnostic radiology practices represented the most common practice types to offer breast MRI screening, reflecting their propensity for early adoption of advanced imaging modalities for new indications such as screening. 26 Most facilities offering supplemental MRI screening were also located in urban settings.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, women with low-income levels are less likely to use screening than women with higher income levels [12, 16]. Findings from the Encuesta Nacional de Salud y Nutrición 2012 [17] conducted by the Instituto de Salud Pública showed that women of higher economic status had more breast screening procedures than those of lower economic status.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our proximity-based measure captures potential access, which is likely to be included in women’s decision making about seeking services. We were not able to account for the specific mode of transportation, or the actual use of specific transportation; transportation has been shown to be associated with mammography receipt previously available in our membership [32]. Also, our study only included women with definitive breast cancer surgery, and thus would not account for the effect of travel time on breast cancer treatment among women who do not undergo surgery.…”
Section: Discussionmentioning
confidence: 99%